Probe Method Implementation for Learning Pseudo Trial Press for Enforcers - Gunawati, Dewi; Rustamji, Muh. (Proceeding of International Conference on Teacher Training and Education, 2016)
The study aims to obtain a method for learning pseudo trial press law for law enfocers.The design of this study is action research (participatory research actions) that combines legal research and studies in the education sector.Normative research methods and sociological studies used appropriate phasing in each year. The types of data used in this study include primary and secondary data.Data collection  methods are interviews,questionares,and literature.data processing is carried out thourgh the stages of editing,coding,tabulating.analysis technique using inductive  and deductive thingking.Observation of actual handling of the case became  the foundation for the further utilized to formulate the appropriate method of  fictitious court press law.In the first year  of this study produced findings: a)  identification of two dominant factors typically by law enforcement  officials in the press dispute , namely  the use of Criminal Code offences and negation case particularities press, b)  finding the distinctiveness criteria law enforcement press located on the right to reply  and the role of Press Council in the settlement release applied to the fictitious  trial methods, c) learned of discrepancies in the prototype method fictious court press  law enforcement against actual practice in the field of press due to the design of learning in the one directions and instructional issues that are not collaborative. Furthermore ,the result of this study indicate that a) the dominant factor affecting  the typical law enforcement official in the press dispute actually consists of the application of the dominant offense  in the Criminal Code as an affroat legal snares for members of the press,and did not understand  the uniqueness of dispute  settlement in the groove press releases as Act mandated by the press, b) Uniqueness lies in the settlement conference where the submission of the right of reply,complaints to the press council,until the publication of the Press Council recommendation that preceded  the litigatif, c) discrepancies prototyoe artificial methods of learning trials with the reality of law enforcement is due to the instructional design of the course and instructional problems that actually can be parsed by the collaborative